Gastrointestinal pathophysiology during endurance exercise: endocrine, microbiome, and nutritional influences - Smith, K. A.; Pugh, J. N.; Duca, F. A.; Close, G. L.; Ormsbee, M. J. (European Journal of Applied Physiology, 2021)
Gastrointestinal symptoms are abundant among athletes engaging in endurance exercise, particularly when exercising in increased environmental temperatures, at higher intensities, or over extremely long distances. It is currently thought that prolonged ischemia, mechanical damage to the epithelial lining, and loss of epithelial barrier integrity are likely contributors of gastrointestinal (GI) distress during bouts of endurance exercise, but due to the many potential causes and sporadic nature of symptoms this phenomenon has proven difficult to study. In this review, we cover known factors that contribute to GI distress symptoms in athletes during exercise, while further attempting to identify novel avenues of future research to help elucidate mechanisms leading to symptomology. We explore the link between the intestinal microbiome, the integrity of the gut epithelia, and add detail on gut hormone and peptide secretion that could potentially contribute to GI distress symptoms in athletes. The influence of nutrition and dietary supplementation strategies are also detailed, where much research has opened up new ideas and potential mechanisms for understanding gut pathophysiology during exercise. The etiology of gastrointestinal symptoms during endurance exercise is multi-factorial with neuroendocrine, microbial, and nutritional factors likely contributing to specific, individualized symptoms. Recent work in previously unexplored areas of both microbiome and gut peptide secretion are pertinent areas for future work, and the numerous supplementation strategies explored to date have provided insight into physiological mechanisms that may be targetable to reduce the incidence and severity of gastrointestinal symptoms in athletes.